Management and Outcomes of Patients with Isolated Superficial Vein Thrombosis under Real Life Conditions (INSIGHTS-SVT). (August 2021) - Bauersachs, Rupert; Gerlach, Horst E.; Heinken, Andreas; Hoffmann, Ulrich; Langer, Florian; Noppeney, Thomas; Pittrow, David; Klotsche, Jens; Rabe, Eberhard
Abstract : Objective: Management and outcomes of superficial vein thrombosis (SVT) are highly variable and not well described. Therefore, the INvestigating SIGnificant Health TrendS in the management of SVT (INSIGHTS-SVT) study collected prospective data under real life conditions. Methods: Prospective observational study of objectively confirmed acute isolated SVT. The primary outcome was a composite of symptomatic deep vein thrombosis (DVT), pulmonary embolism (PE), and extension or recurrence of SVT at three months. The primary safety outcome was clinically relevant bleeding. Results: A total of 1 150 patients were included (mean age 60.2 ± 14.7 years; 64.9% women; mean BMI 29.4 ± 6.3 kg/m 2 ). SVT was below the knee in 54.5%, above the knee in 26.7%, above and below the knee in 18.8%. At baseline, 93.6% received pharmacological treatment (65.7% fondaparinux, 23.2% heparins, 4.3% direct oral anticoagulants [DOACs], 14.5% analgesics), 77.0% compression treatment, and 1.9% surgery; 6.4% did not receive any anticoagulation. The primary outcome occurred in 5.8%; 4.7% had recurrent or extended SVT, 1.7% DVT, and 0.8% PE. Clinically relevant non-major bleeding occurred in 1.2% and major bleeding in 0.3%. Complete clinical recovery of SVT was reported in 708 patients (62.4%). Primary outcome adjusted by propensity score and for treatment duration was lower with fondaparinux compared with low molecular weight heparin (4.4% vs. 9.6%; hazard ratio [HR] 0.51; 95% confidence interval [CI] 0.3 – 0.9; p  = .017). On multivariable analysis, associated factors for primary outcome included another SVT prior to the present SVT event (HR 2.3), age per year (HR 0.97), duration of drug treatment per week (HR 0.92), and thrombus length (HR 1.03). Conclusion: At three month follow up, patients with isolated SVT are at risk of thromboembolic complications (mainly recurrent or extended SVT), despite anticoagulation. In this real life study, about one third had received either heparins, oral anticoagulants, or no anticoagulation.